Perception of intoxication in a field study of the night-time economy: Blood alcohol concentration, patron characteristics, and event-level predictors. (January 2018) - Kaestle, Christine E.; Droste, Nicolas; Peacock, Amy; Bruno, Raimondo; Miller, Peter
Abstract: Objective: Determine the relationship of subjective intoxication to blood alcohol concentration (BAC) and examine whether patron and event-level characteristics modify the relationship of BAC to subjective intoxication. Methods: An in-situ systematic random sample of alcohol consumers attending night-time entertainment districts between 10 pm and 3 am on Friday and Saturday nights in five Australian cities completed a brief interview (n = 4628). Participants reported age, sex, and pre-drinking, energy drink, tobacco, illicit stimulant and other illicit drug use that night, and their subjective intoxication and BAC were assessed. Results: Male and female drinkers displayed equally low sensitivity to the impact of alcohol consumption when self-assessing their intoxication (BAC only explained 19% of variance). The marginal effect of BAC was not constant. At low BAC, participants were somewhat sensitive to increases in alcohol consumption, but at higher BAC levels that modest sensitivity dissipated (actual BAC had less impact on self-assessed intoxication). The slope ultimately leveled out to be non-responsive to additional alcohol intake. Staying out late, pre-drinking, and being young introduced biases resulting in higher self-assessed intoxication regardless of actual BAC. Further, both energy drinks and stimulant use modified the association between BAC and perceived intoxication, resulting in more compressed changes in self-assessment as BAC varies up or down, indicating less ability to perceive differences in BAC level. Conclusions: The ability of intoxicated patrons to detect further intoxication is impaired. Co-consumption of energy drinks and/or stimulant drugs is associated with impaired intoxication judgment, creating an additional challenge for the responsible service and consumption of alcohol. Highlights: Large, random in-situ sample of nightlife patrons: BAC levels and event-level contexts unfeasible in lab settings Male and female subjective intoxication show equally low sensitivity to increases in BAC. Polynomial model: at higher BAC, sensitivity worsens until subjective intoxication non-responsive to differences in BAC Main effects: late hour, pre-drinking, and young age systematically biased intoxication upward regardless of actual BAC Interactions: energy drinks and stimulants compress subjective intoxication responses, leading to even worse sensitivity